2006
DOI: 10.1007/s00464-005-0354-8
|View full text |Cite
|
Sign up to set email alerts
|

Malignant gastrointestinal obstruction: endoscopic stenting versus surgical palliation

Abstract: Endoscopic treatment of malignant gastrointestinal obstruction provides an adequate palliation of the symptoms. It is less invasive, avoids the morbidity associated with open gastrojejunostomy, and achieves a faster start to oral food and a shorter hospital stay, leading to a higher quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(47 citation statements)
references
References 18 publications
(16 reference statements)
1
39
0
5
Order By: Relevance
“…In total, 13 studies met the criteria for inclusion in the review [2][3][4][11][12][13][14][15][16][17][18][19][20]. These included 10 retrospective cohort comparison studies, two randomised controlled trials (RCTs) and one prospective cohort comparison study ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 13 studies met the criteria for inclusion in the review [2][3][4][11][12][13][14][15][16][17][18][19][20]. These included 10 retrospective cohort comparison studies, two randomised controlled trials (RCTs) and one prospective cohort comparison study ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the studies included in our metaanalysis are listed in Table 1. The demographics of patients who had undergone ES were matched with those of patients who had undergone GE with respect to age, 8,11-16 sex, 8,12-16 disease, [9][10][11][12][13][14][15][16] American Society of Anesthesiologists class, 8,10,11,14 and the presence of a double stricture (biliary and gastroduodenal). 14,16 Clinical success Seven studies 8,[11][12][13][14][15][16] reported clinical success (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Endoscopic stent placement is associated with a shorter hospital stay, trend towards a lower periprocedural mortality rate, early resumption of oral intake and lower costs in patients with malignant gastric outlet obstruction compared with surgical treatment28 30, 33, 34, 35, 36, 37, at the expense of a greater need for reintervention owing to stent occlusion by food impaction, stent migration or tumour ingrowth27 33, 38.…”
Section: Discussionmentioning
confidence: 99%